User-friendly system (a smartphone app) for reporting violent incidents in the Emergency Department: an Italian multicenter study. - Ramacciati, Nicola; Guazzini, Andrea; Caldelli , Roberto; Rasero, Laura (La Medicina del Lavoro, 2021)
Background: Nurses, particularly emergency nurses, are among the health workers most exposed to workplace violence. Although reporting systems are increasingly used, under-reporting remains high. Recent studies suggest that the use of easy registration systems could facilitate violence reporting. Objectives: To verify if a friendly reporting system based on a Mobile-app can facilitate the reporting of violent episodes and reduce under-reporting. Methods: Twenty emergency departments of five North and Central Italian regions participated in an interventional, multicentric, pre-post study to verify if a user-friendly reporting system based on a mobile app can facilitate the reporting of violent episodes and reduce under-reporting. Results: Three hundred and eighty-four out of 754 potentially eligible nurses answered the short questionnaire at time T0, and 318 registered for the use of the app. One hundred and eighty-nine answered the questionnaire at time T1. The t-Test for Paired Samples, although with a low mean difference, shows a significant difference in the change in the frequency of the reporting of violent episodes. The correlational tests showed no significant differences in the subgroups divided by demographic and professional characteristics. The usability of the app was considered very high. Conclusions: The simplification of the reporting system and the preliminary acquisition of data on the characteristics of the ED and each nurse, can save time and facilitate the reporting, but technology alone is not enough to solve the under-reporting.